2018
DOI: 10.5217/ir.2018.16.3.436
|View full text |Cite
|
Sign up to set email alerts
|

What nutritional factors influence bone mineral density in Crohn's disease patients?

Abstract: Background/AimsBone mineral density (BMD) is often low in patients with Crohn's disease (CD). This study aimed to evaluate the association between nutritional factors and BMD in a group of CD patients.MethodsCD patients 18 years of age or older were included. The body mass index (BMI), waist circumference (WC) and dietary intake were evaluated during two 24-hour recalls. Bone densitometry was performed by dual-energy X-ray absorptiometry of the full body to assess body composition and of the lumbar vertebrae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although in vitro and animal studies suggest that inflammatory cytokines affect BMD, there is insufficient evidence on the relationship between the two in CD patients [ 31 33 ]. Although there are differences in the study conditions, some reports have indicated a relationship between the CRP level and BMD, whereas others have indicated that increased concentrations of inflammatory biomarkers are not a risk factor for BMD reduction; therefore, an effective consensus has not been achieved [ 34 37 ]. In this study, because CRP levels tended to be higher in the ΔZ-score <0 group, we speculate that the BMD may have decreased due to an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro and animal studies suggest that inflammatory cytokines affect BMD, there is insufficient evidence on the relationship between the two in CD patients [ 31 33 ]. Although there are differences in the study conditions, some reports have indicated a relationship between the CRP level and BMD, whereas others have indicated that increased concentrations of inflammatory biomarkers are not a risk factor for BMD reduction; therefore, an effective consensus has not been achieved [ 34 37 ]. In this study, because CRP levels tended to be higher in the ΔZ-score <0 group, we speculate that the BMD may have decreased due to an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro and animal studies suggest that in ammatory cytokines affect BMD, there is insu cient evidence on the relationship between the two in CD patients [31][32][33]. Although there are differences in the study conditions, some reports have indicated a relationship between the CRP level and BMD, whereas others have indicated that increased concentrations of in ammatory biomarkers are not a risk factor for BMD reduction; therefore, an effective consensus has not been achieved [34][35][36][37]. In this study, because CRP levels tended to be higher in the ΔZ-score < 0 group, we speculate that the BMD may have decreased due to an in ammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The study involved the evaluation of body mass index and waist circumference and performing a DEXA scan of the whole body, specifically the lumbar vertebrae and femoral neck. They concluded that patients with a prolonged gastrointestinal condition such as a CD along with nutritional factor deficiency are at an increased risk of developing osteopenia and osteoporosis [ 10 ]. Andreassen et al reported that many studies and publications were conducted on vitamin D and calcium deficiency and metabolic bone disease in CD, while few studies pointed to vitamin K deficiency.…”
Section: Reviewmentioning
confidence: 99%
“…Malnutrition is another factor in osteoporosis. CD leads to malabsorption of dietary nutrients such as iron, vitamin B12, vitamin C, vitamin K, vitamin D, phosphorous, zinc, and potassium [ 10 ]. Vitamin D and calcium play an essential role in bone metabolism and homeostasis.…”
Section: Introductionmentioning
confidence: 99%